Analisis Permintaan Rekreasi Pantai carita Kabupaten Pandeglang, Jawa Barat - Wahyudi . (Buletin Ekonomi Perikanan, 1996)
To date, demand for recreation area tend to increase as consequences increating welfare of people. In respond to this, supply for recreation area do the same as well, either in member or in quality.The Carita Beach is one of the recreation area which is situated in Labuan municipality/district. Market transaction for this recreation area does not behave like other reguler market of goods and services. This is due to the where at characteristics of natural recreation area it self. For this reason, travel cost method is used to estimate demand for Carita Beach recreation area. Original zones of domestic tourist are weapped for this purpose. It can be explained on model estimate that increase in average travel cost tend to reduce demand for recreation of Carita Beach for thousand population. The same pattern occur from model estimate of demand by all population in all zone using simulation of entry ticket.